Familial temporal lobe epilepsy as a presenting feature of choreoacanthocytosis. - Al-Asmi, A; Jansen, A; Badhwar, A; Dubeau, F; Tampieri, D; Shustik, C; Mercho, S; Savard, G; Dobson-Stone, C; Monaco, A; Andermann, F; Andermann, E (2005)
PURPOSE: Choreoacanthocytosis (ChAc) is an autosomal recessive disorder caused by mutations in VPS13A on chromosome 9q21 and characterized by neurodegeneration and red cell acanthocytosis. Seizures are not uncommon in ChAc but have not been well characterized in the literature. We report two ChAc families in which patients presented with temporal lobe epilepsy. METHODS: Detailed medical and family histories were obtained. EEG, video-telemetry, brain magnetic resonance imaging (MRI) with volumetric studies of amygdala and hippocampus, as well as neuropsychological testing were performed. Blood smears were examined for acanthocytosis. Mutation analysis of VPS13A was carried out in five patients. RESULTS: Six patients in three sibships were initially seen with seizures. Age at seizure onset ranged from 22 to 38 years. Seizures preceded other clinical manifestations of ChAc by < or = 15 years. The epileptic aura consisted of a sensation of déjà-vu, fear, hallucinations, palpitations, or vertigo. EEG with video-telemetry showed epileptiform discharges originating either from one or both temporal lobes. Epilepsy was generally well controlled, but some patients had periods of increased seizure frequency requiring treatment with multiple antiepileptic drugs (AEDs). Both families shared a deletion of exons 70-73 of VPS13A, extending to exons 6-7 of GNA14. CONCLUSIONS: Temporal lobe epilepsy may be the presenting feature of ChAc and may delay its diagnosis. Epilepsy in ChAc patients represents a challenge, because seizures may at times be difficult to control, and some AEDs may worsen the involuntary movements. Mutations in VPS13A or GNA14 or both may be associated with clinical features of temporal lobe epilepsy.